TINJAUAN ARSITEKTUR CANDI KEDULAN - Susetyo, Sukawati (Balai Arkeologi Kalimantan Selatan, 2006)
Administratively Kedulan Temple is located at the Kedulan hamlet, Ttrtomartani village, in the district of Kalasan, regensy of Sleman, Daerah lstimewa Yogyakarta. The date of the Kedulan Temple is known based on two inscriptions near the main temple, namely Panangaran and Sumundul temples (869 M). Both inscriptions were from the period of the reign of Sri Maharaja Rakai Kayuwangi. They mention the commennmoration of the building of a dam in Panangaran. The Kedulan Tempele is a Siva temple, as shwon by two Linggayoni, wich is a representation of the God Siva and his Sakti, inside the chamber, in the north, west, and south niches were the statues of Durga, Ganeca and Agastya. In tenns of its architecture (lay out and profile) the Kedulan Temple can be placed in the central Java period. It is interesting to note that there was a kala without a mandible. We know that thus far some experts are of the opinion that the kalas of the Central Jawa period are without mandibles. Furthennare, at the Kedulan Temple there is also a kala with East Javanese prototype, wich is having some kind of hams.